Galectin-3 as a possible marker for increased thrombogenicity in COVID-19. (3rd October 2022) - Puccini, M; Jakobs, K; Friebel, J; Reinshagen, L; Schencke, P A; Haghikia, A; Landmesser, U; Kraenkel, N; Rauch, U
Abstract: Background: Galectin-3 is a β-galactoside-binding lectin that has been described to be overexpressed in inflammation, atherosclerosis, and in myocardial fibrosis. In COVID-19, galectin-3 has been proposed as an important regulator of the inflammatory response and fibrosis processes. The role of galectin-3 as a platelet activator and thrombosis enhancer has been also recently described. However, the role of galectin-3 in the thrombotic risk in COVID-19 hasn't been studied extensively. Methods: Patients with moderate to severe COVID-19 were included in the study. Hospitalized patients with acute respiratory diseases without COVID-19 were examined as controls. We compared the levels of galectin-3, soluble ST2, tissue factor and tissue factor activity (TFa) as well as several other markers of increased thrombogenicity in both groups. The correlations between galectin-3 and coagulation as well as inflammation markers were assessed. The SOFA score was used as a marker for the clinical outcome. Results: 93 patients were included into the study of which 56 were SARS-CoV-2 positive (COV+) and 37 were SARS-CoV-2 negative controls (COV−). Galectin-3 levels were higher in the COV+ group (median 7.10 ng/ml [IQR 4.61–9.81] vs. 5.47 ng/ml [3.63–6.66] p=0.016) as well as the TFa (median 334.48 pM [115.19–632.58] vs. 134.02 pM [86.92–206.66]) and the ST2 levels (median 5.49 ng/ml [2.40–9.28] vs. 2.19 ng/ml [0.66–3.91] p<0.001). We also observed a positive correlation between galectin-3 and IL-6 (r=0.559, p<0.001), ST2 (r=0.332, p=0.005), SOFA score (r=0.441, p=0.003), von Willebrand factor (r=0.401, p<0.001), plasminogen (r=0.361, p=0.001), antithrombin (r=0.453, p<0.001), and D-dimer (r=0.377, p=0.001). Conclusion: In patients with acute respiratory diseases, especially with COVID-19, galectin-3 is a marker for increased hypercoagulability and worse clinical outcome. Galactin-3 might be a useful therapeutic target for patients with COVID-19. Funding Acknowledgement: Type of funding sources: None.